The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3168/jds.2019-16352
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Intra- and inter-individual milk microbiota variability in healthy and infected water buffalo udder quarters

Abstract: The concept that ruminant mammary gland quarters are anatomically and physiologically unrelated has been recently challenged by immunological evidence. How this interdependence reflects on individual quarter milk microbiota is unknown. The aim of the present study was to cover this gap by investigating the interdependence of quarters among the same mammary gland at the milk microbiota level using next-generation sequencing of the V4-16S rRNA gene. A total of 52 samples were included in this study and classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…This was detected in several individuals. Despite factors pertaining to the individual cow, such as immunity and genetics, that are known to influence the udder microbiota 37 , our results indicated that within-individual microbial variation is frequent. This is supported by the fact that certain taxa were often detected in only one quarter, rather than in all four quarters.…”
Section: Discussioncontrasting
confidence: 57%
“…This was detected in several individuals. Despite factors pertaining to the individual cow, such as immunity and genetics, that are known to influence the udder microbiota 37 , our results indicated that within-individual microbial variation is frequent. This is supported by the fact that certain taxa were often detected in only one quarter, rather than in all four quarters.…”
Section: Discussioncontrasting
confidence: 57%
“…Our data suggests that part of the NASM we cultured may have originated from teat canal colonization rather than IMI. The absence of a difference in the proportion of culture positives between healthy and CMT-positive quarters may also be explained through the interdependence of microbiota among the quarters of an individual buffalo [ 41 ]. It has also been shown in dairy cows that an IMI in one single quarter may also evoke an inflammatory response in the other quarters of that animal [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, samples were obtained from quarter milk. There is no information on the independence of each quarter from adjacent quarters in water buffalo, except for the microbiome 17 . In dairy cows, each quarter is anatomically independent and has its vascular system, nervous system, and suspensory apparatus, suggesting that they may be considered independent 52 , 53 , suggesting that they can be regarded as independent.…”
Section: Discussionmentioning
confidence: 99%